Enhanced bioethanol production by evolved Escherichia coli LGE2-H in a microbial electrolysis cell system - Cong Wang; Dongdong Chang; Qi Zhang; Zhisheng Yu (Bioresources and Bioprocessing, 2024)
Abstract Lignocellulose pretreated using pyrolysis can yield clean energy (such as bioethanol) via microbial fermentation, which can significantly contribute to waste recycling, environmental protection, and energy security. However, the acids, aldehydes, and phenols present in bio-oil with inhibitory effects on microorganisms compromise the downstream utilization and conversion of lignocellulosic pyrolysates. In this study, we constructed a microbial electrolysis cell system for bio-oil detoxification and efficient ethanol production using evolved Escherichia coli to overcome the bioethanol production and utilization challenges highlighted in previous studies. In electrically treated bio-oil media, the E. coli-H strain exhibited significantly higher levoglucosan consumption and ethanol production capacities compared with the control. In undetoxified bio-oil media containing 1.0% (w/v) levoglucosan, E. coli-H produced 0.54 g ethanol/g levoglucosan, reaching 94% of the theoretical yield. Our findings will contribute to developing a practical method for bioethanol production from lignocellulosic substrates, and provide a scientific basis and technical demonstration for its industrialized application. Graphical abstract